Joint submission by the CGIAR, the Food and Agriculture Organization of the United Nations (FAO), International Fund for Agricultural Development (IFAD), and the United Nations World Food Programme (WFP): Views on the eleventh technical expert dialogue and third meeting under the ad hoc work programme on the new collective quantified goal on climate finance - Chilambe, Pedro; Kaugure, Liva; Chowdhury, Jahan; Senesi, Swan (2024)
The ninth (TED 9) and tenth (TED 10) Technical Expert Dialogues under the ad hoc work programme (AHWP) on the new collective quantified goal on climate finance (NCQG) were pivotal in advancing the negotiations on the NCQG and moving towards a draft negotiating text. Based on the current co-chairs’ input paper, and without prejudice to Parties’ deliberations on this agenda item, CGIAR, FAO, IFAD and WFP present this joint submission to TED 11 and the third AHWP. This submission aims at highlighting critical elements to be considered at the next meeting under the AHWP concerning agrifood systems, food security, and the quality and allocation of finance.